REKONSTRUKSI KEDUDUKAN AKTA FIDUSIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 TENTANG EKSEKUSI OBJEK JAMINAN FIDUSIA - Ulfia Hasanah (Lembaga Marwah Rakyat, 2022)
The existence of Law Number 42 of 1999 concerning Fiduciary Guarantees is expected to be able to meet legal needs that can further spur national development and guarantee legal certainty as well as provide legal protection for interested parties in guarantee law. In practice, there are differences in interpreting the executorial meaning in fiduciary guarantee certificates which often lead to vigilante actions (eingerichting) or coercion in the execution of goods that are fiduciary objects. The Constitutional Court through Decision Number 19/PUU-XVII/2019 conducted a review of Article 15 paragraph (2) and paragraph (3) of Law Number 42 of 1999 concerning Fiduciary Guarantees against the articles in the 1945 Constitution of the Republic of Indonesia. With this decision the Constitutional Court provide reconstruction of the meaning and significance of the executorial title as referred to in Article 15 paragraph (2) and paragraph (3). So that it has harmonized a fairer legal relationship between creditors (fiduciary recipients) and debtors (fiduciary givers).